What Actually Happened (Cambridge quarterly of healthcare ethics, 2010)
Through one of their members, the ethics committee was fortunate to have access to a prominent Muslim scholar, Abdulaziz Sachedina, and asked for clarification regarding Islamic beliefs regarding eye removal.